Teacher Self-Assessment of their Science and Technics Competences and Professional Development - Blanuša Trošelj, Danijela; Peić Papak, Petra; Zuljan, Darjo (Revija za elementarno izobraževanje, 2021)
In this paper, the authors present the results of an empirical study that formed part of the broader research project, "Culture of Educational Institution as a Factor in Co-Construction of Knowledge," at the University of Rijeka. The research was conducted on a sample of 317 elementary class teachers from Croatia and Slovenia. The authors sought to establish how class teachers assess their professionalism in practice; whether they show statistically significant differences in assessing their professionalism and professional development in practice at different stages of their careers.